The Modern Systematic Status of Insects - Rakhmatov, E. R. (American Journal of Biology and Natural Sciences, 2025)
This article discusses the current state of insect systematics, various hypotheses proposed by scientists, and the taxonomic groups that have undergone changes along with the reasons for these revisions.